Aplikasi Pembelajaran Bahasa Daerah Tontemboan Menggunakan Metode Extreme Programming Berbasis Android - Glendy Koleangan; Vivi Peggie Rantung (Ikatan Ahli Informatika Indonesia, 2024)
Regional languages play an important role in maintaining the cultural identity of a community, but their use is decreasing due to globalization and technological developments. This study aims to preserve the Tontemboan language, a language used by the Tontemboan tribe in Minahasa, through the development of an Android-based learning application using the Extreme Programming (XP) method. The research method used is application development with data collection methods such as interviews and observations, analysis and qualitative data. The results of the study indicate that this application is effective in improving the understanding and use of the Tontemboan language among users. The conclusion of this study is that technology-based learning applications can be an effective tool in preserving regional languages and cultural heritage.